Natural convection and entropy generation inside porous square cavity with undulated vertical walls under four heating scenarios - Mouna, Maache; Chihab Eddine, Brahmi; Nourredine, Belghar; Mahmoud, Kalfali (Vojnotehnički glasnik / Military Technical Courier, 2026)
Introduction/purpose: This work studies natural convection within a porous cavity with undulated vertical walls focusing on investigating the effects of various heating scenarios. The model consists of a square cavity with sinusoidal undulations on its vertical walls. The cavity is characterized by a square cross-section, and the undulations are described by a sinusoidal wave function with a specific amplitude and wavelength. The left vertical wall of the cavity is maintained at a constant cold temperature, while the bottom wall is subjected to various heating profiles, including linear heating, constant heating, parabolic heating, and sinusoidal heating. The choice of these different heating scenarios is intended to explore how the heat transfer behavior changes under each condition. The top and right walls are assumed to be adiabatic. Methods: The effects of heating methods and Darcy number on fluid flow and heat transfer in the cavity under a high Rayleigh number are numerically analyzed. Results: Results show that all heating profiles create distinct thermal gradients, influencing the vortex strength and flow complexity. The study also investigates the irreversibilities within the system, focusing on entropy generation due to both heat transfer and fluid friction, to evaluate the thermodynamic efficiency of the cavity. Conclusion: The study aims to provide a comprehensive understanding of how heating conditions, permeability variations and high Rayleigh number convection affect the thermal and fluid dynamics in porous cavities, with implications for improving the performance of thermal management systems in practical engineering applications.